The role of orthodontic in temporomandibular disorder treatment: Peran ortodonti dalam penanganan temporomandibular disorder - Asma, Rezki Nur; Ranggang, Baharuddin M. (Makassar Dental Journal PDGI Makassar, 2025)
Temporomandibular disorder (TMD) is the main cause of non-dental pain in the orofacial area. The causes and mechanisms of TMD are not yet fully understood. Generally, there are many factors that contribute to TMD, or mechanisms that exacerbate the condition. One of the primary causes of TMD is malocclusion. This study discusses the role of orthodontic treatment in managing TMD. Orthodontics is one of the treatments used to address this condition. Orthodontic treatment is one of the definitive long-term treatments for patients with various temporomandibular joint disorders through the proper use of various orthodontic ap-pliances. Therefore, orthodontic treatment is expected to improve oral health, functionality, and aesthetic appearance. It is con-cluded that orthodontic treatment can balance the bite of the upper and lower jaws, thereby achieving a normal bite.